2015
DOI: 10.1007/s12263-015-0475-1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and n-3 polyunsaturated fatty acid supplementation have a synergistic hypotriglyceridemic effect in ovariectomized rats

Abstract: The n-3 polyunsaturated fatty acids (PUFAs), EPA and DHA, as well as estrogen have been shown to decrease circulating levels of triglyceride (TG), but their underlying mode of action is unclear. The purpose of this study was to determine the effects of n-3 PUFA consumption and estrogen injection on TG metabolism. Rats (n = 48) were fed a modified AIN-93G diet with 0, 1, or 2 % EPA ? DHA relative to the total energy intake during 12 weeks. At 8 weeks, rats were ovariectomized (OVX), and after a 1-week recovery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our previous study showed that hepatic content of triglycerides was decreased by the downregulation of hepatic triglyceride synthesis and the upregulation of hepatic triglyceride oxidation in rats fed n-3 PUFA [34]. In addition, meta-analysis of randomized controlled trials showed that n-3 PUFA supplementation improved liver steatosis and liver function in patients with NAFLD [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that hepatic content of triglycerides was decreased by the downregulation of hepatic triglyceride synthesis and the upregulation of hepatic triglyceride oxidation in rats fed n-3 PUFA [34]. In addition, meta-analysis of randomized controlled trials showed that n-3 PUFA supplementation improved liver steatosis and liver function in patients with NAFLD [13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The lower prevalence of NAFLD in women is speculated to be, at least in part, due to the protective effects of estrogen. Animal studies have shown that estrogen treatment to male or oophorectomized female rats decreases IHTG content (Toda et al 2001;Kim et al 2015;Jin et al 2017). Furthermore, the risk of developing NAFLD increases in women post-menopause when estrogen decreases (Ryu et al 2015).…”
Section: Sex Differences In Hepatic Lipid Storagementioning
confidence: 99%
“…Consistent with our results, previous studies reported that oestrogen increases hepatic and blood levels of DHA but not EPA ( 8 , 41 ) . Oestrogen also increases the hepatic expressions of FADS2 ( 8 ) , ELOVL2 ( 42 ) and ELOVL5 ( 43 ) , which are modulated by increased PPAR- α ( 7 ) and decreased SREBP1 ( 44 ) . However, Kitson et al ( 8 ) reported that oestrogen has no effect on the hepatic expression of FADS1, converting 20 : 4 n -3 to EPA, which is consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%